lore - McCombs, Davis, 1969- (Book collections on Project MUSE., 2016)
"Drawn from the rich folk traditions of his native Mammoth Cave region in Kentucky as well as the folklore of his adopted Ozark Mountains of Arkansas, the poems in Davis McCombs's third collection exist along the fraught lines where nature and agriculture collide or in those charged moments where modernity intrudes on an archaic world. These poems celebrate out-of-the-way places, the lore of plants, wild animals and their unknowable lives, and nearly forgotten ways of being and talking and doing. Rendered in a language of great lexical juxtapositions, here are days of soil and labor, nights lit only by firelight, and the beings, possibly not of this world, lured like moths to its flames. McCombs, always a poet of place and of rootedness, writes poems teetering between two locales, one familiar but achingly distant, one bewildering but alluringly present"--